Bio-inspired nanocomposite by layer-by-layer coating of chitosan/hyaluronic acid multilayers on a hard nanocellulose-hydroxyapatite matrix. (15th October 2019) - Huang, Chen; Fang, Guigan; Zhao, Yangyang; Bhagia, Samarthya; Meng, Xianzhi; Yong, Qiang; Ragauskas, Arthur J.
Highlights: CNCs/HAP matrix was synthesized by a facile in situ HAP coating on CNCs. The HAP coating significantly improved the mechanical property of the matrix. LBL assembly on the hard CNCs/HAP matrix was established with chitosan and hyaluronic acid. Abstract: This study proposed a layer-by-layer technique on the hard CNCs/hydroxyapatite (HAP) matrix using biodegradable and biocompatible chitosan and hyaluronic acid (HA). Inspired by the mineralized collagen in human bone, the CNCs/HAP matrix was synthesized by a facile in situ HAP coating on the CNCs fibers. The chemical and crystalline structure of the CNCs/HAP matrix was investigated with FTIR, XRD, HRTEM, and SAED. The surface of the CNCs/HAP matrix was analyzed by AFM which showed a flat structure with a roughness of 23.12 nm, however, the surface roughness increased to 56.09 nm with the assembly of chitosan and HA. After the LBL assembly, the surface hydrophilicity of the CNCs/HAP films was improved. Moreover, the CNCs/HAP matrix showed enhanced mechanical property than pure CNCs matrix. Although there is compromise in the mechanical property after the LBL assembly, it is anticipated its bioaffinity and biocompatibility will increase with the incoporation of chitosan and HA.